Adhesive resistance analysis of glass fiber pins submitted to extrusion mechanical testing of scissors in different cement protocols (Research, Society and Development, 2022)
The aim was to evaluate the shear strength by extrusion and check the type of fiberglass pin failure who received different surface treatments to test the Single Bond Universal® multi-purpose adhesive (3M ESPE). Eighty bovine incisors with endodontic treatment were randomly divided into four groups. Group I: the pins received application of silane; Group II: no treatment; Group III: Silane and Adhesive; And Group IV: adhesive only. The groups were submitted to thermal cycling for 5,000 cycles, the roots were sectioned and submitted to the push out test. With the silanization and the application of the adhesive, the resistance between the fiberglass pin and the dentin of any of the root thirds was significantly lower. The silane-adhesive association caused significant damage to the adhesion. Silanization alone constituted the treatment that improved adhesion. Adhesive defects were the most prevalent.